Chargement de la page en cours... 


ÊãÇÑíä &ael

               &





 

                            sinx - sinx*  / cosx - cosx*






                    sinx - sinx* / cosx - cosx*



                   = sinx(1 - sinx) / cosx(1 - cosx)



                               on sait que   sinx = 1 - cosx  et  cosx = 1 - sinx
                        alors:
                  =sinx cosx / cosx sinx


                      si : x # pi / 2 + k pi   et  x # k pi    alors :


                 sinx - sinx* / cosx - cosx*  =  1